Millennium Development Goals and International Year of Microfinance 2005 in Nepal - Sharma, Puspa Raj (Journal of Nepalese Business Studies, 2007)
No single intervention can defeat poverty. Poor people need employment, schooling and health care. Some of the poorest require immediate income transfers or relief to survive. Access to financial service forms a fundamental basis on which many of other essential interventions depend. Moreover, improvement in health care, nutritional advice and education can be sustained only when households have increased earnings and greater control over resources. Financial services thus reduce poverty and its effect in multiple, concrete ways. And the beauty of microfinance is that, it emphasizes to women empowerment and self dependent financial approach. It emphasizes the financial sustainability also, which can contribute far beyond the limits of scarce donors. In this arena, International Year of Microfinance 2005 substantially contributes to achieve Millennium Development Goals (MDGs). Journal of Nepalese Business Studies Vol.2(1) 2005 pp.87-94